SOLVE MULTI-OBJECTIVE QUADRATIC ASSIGNMENT PROBLEMS USING THE FISH SWARM ALGORITHM FOR THE INTERNAL ARRANGEMENT OF HOSPITAL FACILITIES - Moamar Shakir Mahmood; Abdelkarim Ben Habib Elloumi; Enas Abbas Abed (Scholars Digest Publishing, 2024)
This study aims to study methods for solving multi-objective quadratic assignment problems using the fish swarm algorithm, by reviewing the literature related to the algorithm, identifying variables and criteria necessary to evaluate its performance, designing the study, and applying the algorithm to hospitals. The collected data is analyzed to provide results and recommendations, which contributes to improving quadratic allocation processes within the hospital and achieving the research goal. The study concluded that the fish swarm algorithm shows a high level of efficiency in solving multi-objective quadratic mapping problems to reduce distances traveled within hospitals. The algorithm demonstrated the ability to improve planning and distribution of resources within hospitals. The algorithm also demonstrated the ability to improve the patient experience, which contributed to improving the efficiency of operations and reducing the time required to move between different places within the hospital.
Keywords: multi-objective quadratic assignment problems, fish swarm algorithm, hospital.